Use of pesticides in the irrigation district 075 of North Sinaloa, Mexico - Arciniega Galaviz, Marco Arturo (Technium Sustainability, 2024)
The state of Sinaloa is known to be a large agricultural producer in Mexico. The use of pesticides in this region is in large quantities, which affects a large number of agricultural workers due to exposure to these chemicals. The objective of this work to identify the main crops, pests and pesticides used in the Irrigation District 075 for this research work a convenience sampling was carried out and 100 surveys were applied with questions related to the pests, crops and pesticides used by the workers agriculture in this region of northwestern Mexico. According to the results, the main crops planted and harvested are corn and beans, the main pests are the fall armyworm (Spodoptera frugiperda) and the whitefly (Trialeurodes vaporariorum) and the main pesticides are Tamaron and Cypermethrin. In conclusion, agricultural workers in Irrigation District 075 use pesticides considered of medium and high toxicity and have a preference for chemical control over biological control